A Review of Current SPSS Products: SPSS 12, SigmaPlot 8.02, SigmaStat 3.0, Part 1. - Hilbe, Joseph M. (American Statistician, 2003)
A review of three SPSS Inc. software packages, SPSS 12, SigmaPlot 8.02, and SigmaStat 3.0, is presented.